Encapsulated Papillary Carcinoma in an Elderly Male Whose Diagnosis Was Difficult before Surgery: A Case Report - Maho Sugino; Yoshiya Horimoto; Fumi Murakami; Yuka Takahashi; Kazutomo Ouchi; Hideaki Sato; Yasunori Ishido (Case Reports in Oncology, 2023)
Encapsulated papillary carcinoma (EPC) is a relatively rare histologic type of breast cancer. It is sometimes difficult to obtain a definitive diagnosis by needle biopsy, reflecting its characteristics as an intracystic lesion. Herein, we report a case of EPC in an elderly male that was difficult to diagnose before surgery. A 70-year-old man visited our hospital after a mass just under his right nipple that gradually increased in size. Ultrasonography revealed a well-defined intracystic 50 mm-sized tumor and a papillary-shaped solid component arising from the cyst wall. Cytology revealed small clusters of atypical cells suggestive of malignancy, but we did not reach a definitive diagnosis with subsequent vacuum-assisted needle biopsy due to the small amount of specimen. Given the imaging findings strongly suggested a malignant tumor, a mastectomy was performed. Histologically, there was a thick fibrous capsule and mildly atypical cells showed papillary growth, and we diagnosed the case as EPC (pTisNXM0). Sometimes, EPC is difficult to discriminate from intracystic papilloma before surgery, but clinicians should always keep in mind that this histological type exists with a certain frequency in male patients.